The Transformations Of The Novelistic Canon: The Comparison Of Daniel Defoe’s And Penelope Aubin’s Dedication To Truth And Virtue - Maciulewicz Joanna (Studia Anglica Posnaniensia, 2014)
The aim of the article is to discuss the evolution of the concept of the literary canon in the context of eighteenth-century fiction. The concept of the literary canon has been traditionally associated with timeless, universal values which transcend the ideological conditions of the period in which texts are created. In present criticism, which is shaped by cultural studies, the association of a canon with universality has been challenged. A canon has been recognised by cultural critics as an instrument of an ideological power struggle which presents the values of dominant social groups as universal. The analysis of novels written by Penelope Aubin and Daniel Defoe at the beginning of the eighteenth century demonstrates that the study of literature only from an ideological viewpoint does not account for the workings of the literary canon. Both Aubin and Defoe employ the same formula of fiction, adventure story with a moral commentary, but while Defoe’s fiction has survived in literary histories, Aubin’s stories, after their initial success, fell into oblivion and have been rediscovered only recently by feminist critics. The varying fates of Aubin’s and Defoe’s fiction point to the insufficiency of the definition of canon which binds literary value too strongly with ideology.